Persepsi Ibu HamilTentang Kebutuhan Asam Folat, Zat Besi, Dan Kalsium Sebagai Persiapan Kehamilan Di Kota Mataram Dan Kabupaten Lombok Barat - Setyawati, Irni; Handayani, Sri (Universitas Qamarul Huda Badaruddin, 2018)
The Indonesian Demographic and Health Survey (IDHS) in 2012 found complications during pregnancy nationally by 24%, while those in the province of West Nusa Tenggara were still above the national figure of 33%(4). Complications during pregnancy can be caused by various factors, one of which is the absence of pregnancy preparation before conception. Women with a history of merariq on Lombok in 2015 did not make preparations for pregnancy either from their supplemental consumption and health behavior(8). The purpose of this study was to identify differences in pregnancy preparation based on the mother's perception of the need for folic acid, iron and calcium in the city of Mataram and West Lombok regency. This study was comparative analytical with a retrospective approach. The number of samples obtained was 64 people. The sampling technique was purposive sampling. The study was conducted at the Health Center in Mataram City and West Lombok district in September - October 2017. Variables were measured using a questionnaire and analyzed using the Chi-Square test. Most respondents did not prepare for pregnancy and had the perception that they needed to consume folic acid, but did not need to consume iron and calcium. There were significant differences in preparation for pregnancy between mothers who perceived the need to consume folic acid and iron (value of p <0.05). Respondents' perceptions of the need to consume folic acid, iron and folic acid affect pregnancy preparation conducted by mothers. It is expected that further research on the factors that influence pregnancy preparation.